Phenomenon of “Creativity” in Nicolas Berdyaev‘s Philosophy (Forum Theologicum Sardicense, 2025)
Olga Dramancheva, Phenomenon of “Creativity” in Nicolas Berdyaev’s Philosophy.
Keywords: Николай Бердяев; Russian Religious Philosophy; Religious Studies; Russian Thinkers; Russian Orthodoxy